Critical Study Of Muhammad Syahrur's Hermeneutics On The Veil And Its Relevation In The Indonesian Context - Robiatus Soleha, Robiatus Soleha; Safrudin Edi Wibowo; Uun Yusufa (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The developments that continued until the 19th century were the starting point for the revival of the Arab world. A strong desire to rise to what is called the era of modernity. One form of responding to the progress of knowledge in Islamic studies is the emergence of academics or researchers with various innovations they promote. One of them is Muhammad Syahrur. He is a well-known reformer in the world of interpretation of the Qur’an and Hadith. The breakthroughs made in reinterpreting the texts made him a barometer for analyzes in studying the texts of the Qur'an and Hadith. The empirical framework of thinking through the hudud theory approach which is used as an approach in interpreting the Qur’an makes him a progressive Islamic figure who tries to escape the influence of the hegemony of classical interpretation which he considers no longer able to answer the problems of the reality of a quite dynamic society. This research will focus on Syahrur's perspective in reinterpreting the concept of the veil in the Qur’an. This research will attempt to reveal the differences between Syahrur's interpretation and classical ulama and how it is relevant to the realities of contemporary society.